Investigation of the Influence of Atmospheric Scattering on Photolysis Rates Using the Cloud-J Module - Anastasia Imanova; Eugene Rozanov; Sergei Smyshlyaev; Vladimir Zubov; Tatiana Egorova (Atmosphere)
This study analyses the wide-band algorithm, Cloud-J v.8.0, from the point of view of the validity of the choice of wide spectral intervals to accelerate the calculations of photolysis rates in the lower and middle atmosphere, considering the features of solar radiation propagation, and to assess the influence of the processes of reflection and scattering on molecules, aerosols, and clouds. The results show that the calculations performed using Cloud-J v.8.0 are in agreement with the data obtained using the high-resolution LibRadtran model. The study also considers the factors influencing the propagation of the solar flux through the atmosphere in Cloud-J v.8.0, which occurs following theoretical concepts. It is shown that the presence of cloud layers can increase photolysis rates by up to 40% in the above-cloud layer and decrease them by up to 20% below the cloud layer. The presence of volcanic aerosol can increase the photolysis rates in the upper part of the layer and above it by up to 75% and decrease them by up to 75% in the underlying atmosphere. Rayleigh scattering can both enhance photolysis rates in the troposphere and reduce them at large zenith angles. Thus, Cloud-J offers a robust method for modelling atmospheric photodissociation processes with high computational efficiency.